Meningkatkan Hasil Belajar Melalui Model Project Based Learning Pada Matakuliah Jaringan Komputer - I Wayan Sugianta Nirawana (CV. Aksara Global, 2023)
: Limitations in komputer network practicum, causing only relying on theory and tests. During the pre-test, there were 8 students whose learning outcomes had not been completed. This study aims to improve student learning outcomes using project-based learning models. The object of this research is students in the 4th semester of komputer education, FKIP, Universitas Mulawarman. The software used in making the project is a Cisco packet tracer with a choice of komputer network projects. The type of research used is classroom action research in the form of projects and tests to get maximum learning outcomes. Learning outcomes are obtained from a combination of project scores and tests from cycle I and cycle II. Based on the research results in cycle I and cycle II, it can be concluded that there is an increase in student learning outcomes through the application of project-based learning. Suggestions for research need to examine other variables such as creativity and learning activities because project-based learning requires a lot of observation of group work in monitoring. in the classroom